Data‐driven detailed hair animation for game characters. (3rd May 2016) - Wu, Chenlei; Kanai, Takashi
Abstract: We propose a data‐driven method to realize high‐quality detailed hair animations in interactive applications like games. By devising an error metric method to evaluate hair animation similarities, we take hair features into consideration as much as possible. We also propose a novel database construction algorithm based on Secondary Motion Graph. Our algorithm can improve the efficiency of such graphs to reduce redundant data and also achieves visually smooth connection of two animation clips while taking into consideration their future motions. The costs for the run‐time process using our Secondary Motion Graph are relatively low, allowing real‐time interactive operations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We propose a data‐driven method to realize high‐quality detailed hair animations in interactive applications like games. By devising an error metric method to evaluate hair animation similarities, we take hair features into consideration as much as possible. We also propose a novel database construction algorithm based on Secondary Motion Graph. Our algorithm can improve the efficiency of such graphs to reduce redundant data and also achieves visually smooth connection of two animation clips while taking into consideration their future motions.